The rationale for a safe asset and fiscal capacity for the Eurozone - Lorenzo Codogno; Paul van den Noord (London School of Economics and Political Science (LSE), European Institute, 2019)
The only way to share common liabilities in the Eurozone is to achieve full fiscal and political union, i.e. unity of liability and control. In the pursuit of that goal, there is a need to smooth the transition, avoid unnecessary strains to macroeconomic and financial stability and lighten the burden of stabilisation policies from national sovereigns and the European Central Bank, while preserving market discipline and avoiding moral hazard. Both fiscal and monetary policy face constraints linked to the high legacy debt in some countries and the zero-lower-bound, respectively, and thus introducing Eurozone 'safe assets' and fiscal capacity at the centre would strengthen the transmission of monetary and fiscal policies. The paper introduces a standard Mundell-Fleming framework adapted to the features of a closed monetary union, with a two-country setting comprising a 'core' and a 'periphery' country, to evaluate the response of policy and the economy in case of symmetric and asymmetric demand and supply shocks in the current situation and following the introduction of safe bonds and fiscal capacity. Under the specified assumptions, it concludes that a safe asset and fiscal capacity, better if in combination, would remove the doom loop between banks and sovereigns, reduce the loss in output for both economies and improve the stabilisation properties of fiscal policy for both countries, and thus is welfare enhancing.
Keywords: 330; Fiscal policy; Business fluctuations; Safe sovereign assets; Fiscal capacity